1988
DOI: 10.1038/bjc.1988.43
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adenocarcinoma of the cervix: a case-control study

Abstract: Summary To assess risk factors for cervical adenocarcinoma data were collected in a case-control study of 39 cases and 409 controls conducted in the greater Milan area. Questions were asked about personal characteristics and habits, gynaecologic and obstetric data, history of lifetime use of oral contraceptives and other female hormones, and general indicators of sexual habits (age at first intercourse and total number of sexual partners). The relative risk of cervical adenocarcinoma increased with number of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
2

Year Published

1988
1988
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 21 publications
1
23
2
Order By: Relevance
“…Sexual behaviour, and in particular the number of sexual partners, is strongly associated both with HPV infection and with the risk of squamous cell carcinoma of the cervix. Most controlled studies have also found the risk of cervical adenocarcinoma to increase directly with the lifetime number of sexual partners (Brinton et al, 1987;Parazzini et al, 1988;Ursin et al, 1996;Chichareon et al, 1998;Madeleine et al, 2001;Altekruse et al, 2003), and studies providing a direct comparison have found no differences in risk between adenocarcinoma and squamous cell carcinoma in all and in HPV-positive women (Brinton et al, 1987;Horowitz et al, 1988;Brinton et al, 1993;Chichareon et al, 1998;Ngelangel et al, 1998). Our results are consistent with existing evidence.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Sexual behaviour, and in particular the number of sexual partners, is strongly associated both with HPV infection and with the risk of squamous cell carcinoma of the cervix. Most controlled studies have also found the risk of cervical adenocarcinoma to increase directly with the lifetime number of sexual partners (Brinton et al, 1987;Parazzini et al, 1988;Ursin et al, 1996;Chichareon et al, 1998;Madeleine et al, 2001;Altekruse et al, 2003), and studies providing a direct comparison have found no differences in risk between adenocarcinoma and squamous cell carcinoma in all and in HPV-positive women (Brinton et al, 1987;Horowitz et al, 1988;Brinton et al, 1993;Chichareon et al, 1998;Ngelangel et al, 1998). Our results are consistent with existing evidence.…”
Section: Discussionsupporting
confidence: 91%
“…Munoz et al (2002), in a pooled analysis of 10 case -control studies in HPV-positive women, found that the risk of squamous cell carcinoma increased with the number of fullterm pregnancies; there was no equivalent trend in the risk of adenocarcinoma and adenosquamous carcinoma, although the risk of adenocarcinoma was higher in parous women than in nulliparous. Most other case -control studies, including those taking HPV infection into account, have shown an association with parity for squamous cell carcinoma of the cervix (Brinton et al, 1987Parazzini et al, 1988;Hildesheim et al, 2001;Altekruse et al, 2003) but, with the exception of one study (Parazzini et al, 1988), not for adenocarcinoma (Brinton et al, 1987Ursin et al, 1996). Altekruse et al (2003) found an inverse relationship between parity and cervical adenocarcinoma risk.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our data are in agreement with the findings of Brinton et al (1987b) who observed no association with parity, and lend support to previous results which have indicated differing aetiologies for squamous cell carcinomas and adenocarcinomas of the cervix uteri (Menczer et al, 1978;Silcocks et al, 1987). However, our results contrast with findings of Parazzini et al (1988). In a recent case-control study of 39 women with adenocarcinoma of the cervix they observed increased risk with increasing number of pregnancies and early age at first birth.…”
Section: Discussioncontrasting
confidence: 44%